2007
DOI: 10.1021/jp068661r
|View full text |Cite
|
Sign up to set email alerts
|

C78 Cage Isomerism Defined by Trimetallic Nitride Cluster Size:  A Computational and Vibrational Spectroscopic Study

Abstract: Molecular structures of Dy(3)N@C(78) and Tm(3)N@C(78) clusterfullerenes are addressed by the IR and Raman vibrational spectroscopic studies and density functional theory (DFT) computations. First, extensive semiempirical calculations of 2927 isomers of C(78) hexaanions followed by DFT optimization were applied to establish their relative stability. Then, DFT calculations of a series of M(3)N@C(78) (M = Sc, Y, Lu, La) isomers were performed which have shown that the stability order of the isomers depends on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
173
0
9

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(192 citation statements)
references
References 47 publications
10
173
0
9
Order By: Relevance
“…The first reports of EMFs with carbon cages containing fused pentagon systems were those of Sc 2 @C 66 [115] and Sc 3 N@C 68 (D 3 :6140). [110] Other examples are [75b, 104,[116][117][118][119][120][121] On the other hand, spectroscopy along with DFT calculations strongly suggested that the major isomer of Dy 3 N@C 78 and Tm 3 N@C 78 both have the non-IPR carbon cage of symmetry C 2 :22 010 [122] and that Ce 2 @C 72 possesses a non-IPR carbon cage of D 2 symmetry, as in the case of La 2 @C 72 . [123] It is interesting to note that as the size of the fullerene increases, the number of fused pentagon systems decreases; for example, Sc 3 N@C 68 (D 3 :6140) has three fused pentagon systems while Gd 3 N@C 82 (C s :39 663) and M 3 N@C 84 (C s :51 365) (M = Gd, Tb, Tm) have only one ( Figure 5).…”
Section: Violations Of the Ipr With Emfsmentioning
confidence: 99%
“…The first reports of EMFs with carbon cages containing fused pentagon systems were those of Sc 2 @C 66 [115] and Sc 3 N@C 68 (D 3 :6140). [110] Other examples are [75b, 104,[116][117][118][119][120][121] On the other hand, spectroscopy along with DFT calculations strongly suggested that the major isomer of Dy 3 N@C 78 and Tm 3 N@C 78 both have the non-IPR carbon cage of symmetry C 2 :22 010 [122] and that Ce 2 @C 72 possesses a non-IPR carbon cage of D 2 symmetry, as in the case of La 2 @C 72 . [123] It is interesting to note that as the size of the fullerene increases, the number of fused pentagon systems decreases; for example, Sc 3 N@C 68 (D 3 :6140) has three fused pentagon systems while Gd 3 N@C 82 (C s :39 663) and M 3 N@C 84 (C s :51 365) (M = Gd, Tb, Tm) have only one ( Figure 5).…”
Section: Violations Of the Ipr With Emfsmentioning
confidence: 99%
“…has been achieved during recent years. [24-26, 28-30, 32-37, 39, 40, 45, 49-53] Many of them have been structurally characterized by X-ray diffraction, the largest being Tb 3 N@C 88 . [54] The derivatization of MNEFs by means of typical organic reactions, such as Diels-Alder, [26,31,55,56] 1,3-dipolar cycloaddition of azomethine ylides, [25,27,[57][58][59] and BingelHirsch cyclopropanation, [60,61] has also been performed.…”
Section: Introductionmentioning
confidence: 99%
“…One suggestion is that all free electrons from metal atoms should be localized in the carbon cage, therefore a metal atom and carbon cage would form an ionic model of bonding (as a ligand). The charge of the carbon cage has been confirmed by some theoretical [90][91][92][93][94][95] and experimental 87,[96][97][98][99] results. Other studies on various EMFs established that was a smaller charge on the metal atom than was expected in the anion-cation structure 88,[100][101][102][103][104][105][106] and pointed toward the hypothesis of covalent bonding.…”
mentioning
confidence: 56%
“…In this case, the LUMO of EMFs is localized in the metal atom. 94,110,111 Fullerenols ( Figure 5) differ from other fullerene derivatives. These molecules behave as proton conductivity materials.…”
mentioning
confidence: 99%